PENGARUH PEMBERIAN SARI KURMA TERHADAP LAMA KALA II PADA IBU PRIMIPARA - Indreswati, Liwalidayya Swita Ayu (Maternal Child Health Care, 2022)
Prolonged labour is one of the pathological forms of labor. Manggopoh Community Health Center is one of the health centers have high reports of childbirth complications. They are 121 (23%) cases, dominated by cases of prolonged labor. This study aimed to determine The Effect of Dates Extract on Second Phase on Primipara Mothers in the Working Area of Manggopoh Community Health Center in 2021. The type of research was a quasi-experimental approach with pos test only with control group design approach. The population in this study were all maternity mothers in the working area of Manggopoh Community Health Center, as much as 44. By using purposive sampling technique, 32 people were chosen as the samples. The data were collected through observation sheets and it was analyzed by univariate analysis and bivariate analysis using t-independent test. The results showed that the administration of date palm juice had a significant effect on the length of the second stage of labor with an average difference of 4.875 minutes in the second stage of labor and p value = 0.001, where the length of the second stage of labor was shorter in the experimental group. It can be concluded that the administration of date palm juice at the end of pregnancy has a significant effect on the length of the second stage of labor. It is hoped that the Manggopoh Community Health Center will provide health information to pregnant women to always prepare themselves both physically and mentally in facing childbirth, one of them is by utilizing date palm juice at the end of pregnancy which is proven to be effective in the progress of labor. Keywords : Dates, Labor, Stage II